Factors associated with nursing students' willingness to care for older adults in Korea and the United States - Insun Jang; Doonam Oh; Yeon Sook Kim (Elsevier, 2019)
Objective: Elderly health care needs increase and nurses' role for elderlies is vital. It is significant to identify nursing students' intention to care for elderlies. Thus, this study investigated nursing students' willingness to care for elderlies in Korea and the United States. Methods: The study was conducted with 437 undergraduate nursing students from Korea and the United States from May 25 to 31, 2018. Participants completed a survey including frequency and quality of contact, anxiety about aging, empathy, attitude toward elderly, and willingness to care. Results: Study findings from the entire group showed that nursing students' willingness to care for the elderly was positively associated with contact quality (β = 0.22, P < 0.001) and empathy (β = 0.12, P = 0.009) but negatively associated with anxiety about aging (β = −0.23, P < 0.001) and attitude toward the elderly (β = −0.14, P = 0.004). Contact quality (β = 0.30, P < 0.001) was positively associated with the willingness to care in Korean students, whereas extended family living type (β = −0.15, P = 0.012) and attitude toward the elderly (β = −0.18, P = 0.005) negatively associated in US students. Conclusion: This study suggested that nursing educators reinforce contact quality and empathy but reduce anxiety about aging and attitude toward elderly to enhance future nurses' care quality. Keywords: Attitude, Baccalaureate nursing education, Elderly, Empathy, Nursing care, Republic of Korea, United States